The Role of School Leadership in Improving the Quality Management of Education at SMA Kabupaten Kutai Barat - Afriyanti; Radiyah, Titi; Azainil (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the role of school leadership in enhancing the quality management of education at SMAN 2 Linggang Bigung, Kutai Barat Regency. The methodology employed in this research is a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and documentation studies involving the principal, teachers, and representatives of the school committee. The findings indicate that the diversity of leadership styles, such as participative, transformational, and collaborative, significantly contributes to the improvement of educational quality. The strategies implemented, including teacher training, project-based learning, and parental involvement, have had a positive impact on the quality of learning and student motivation.Despite challenges such as budget constraints and resistance from some teachers, the collaborative efforts made by the principal demonstrate great potential for improving educational quality in the region. This research emphasizes the importance of inclusive leadership and adaptive strategies in creating an effective learning environment. The principal should continue to strengthen collaboration with various stakeholders and develop structured training programs for teachers to enhance their competencies in implementing innovative teaching methods. With these measures, it is hoped that SMAN 2 Linggang Bigung can continue to improve educational quality and produce graduates who are ready to compete in the global era. Keywords: 1st School Leadership, 2nd The Quality Management, 3rd Education, 4th SMA,